Multiple myeloma - Dimopoulos, M.A.; Terpos, E. (Annals of Oncology, 2010)
Multiple myeloma (MM) is the second most common hematological malignancy, with an incidence of 6/100 000 in Europe. Interactions between myeloma cells and the microenvironment are essential for MM cell survival. Better knowledge of disease biology has led to the introduction of novel agents for the management of myeloma patients. Patients with asymptomatic MM may remain stable for a long time without any therapy, and treatment is needed only in symptomatic disease. Patients who are eligible for high-dose therapy and autologous stem cell transplantation (ASCT) are usually treated with bortezomib- or immunomodulatory drug (IMiD)-based regimens as induction therapy pre-ASCT. In elderly patients, the combination of melphalan and prednisone with either thalidomide (MPT) or bortezomib (MPV) is considered as the standard of care in this setting. Novel agent-based therapies are used for the management of relapsed/refractory disease. However, previous therapies, age, comorbidities and drug safety have to be taken into consideration before deciding the appropriate therapy for patients with relapsed/refractory myeloma. Patients with renal impairment or with extended bone disease may be treated with bortezomib-based regimens, while patients with pre-existing peripheral neuropathy may be treated with lenalidomide-based combinations. Maintenance therapy with thalidomide can be administered post-ASCT; however, caution is needed due to thalidomide toxicity. © The Author 2010. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved.
Keywords: multiple myeloma; novel agents; Survival; therapy